(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The period of the Republican era was characterized by the growth of state supervision over social bodies and institutions, as the social care sector flourished as it established many social institutions in the country, opening more homes for orphans and elderly care, in addition to that increasing the number of specialists in this important field, and we also find that these institutions relied on The state’s financing of it, through funds allocated in the state budget, is the services provided by social welfare institutions to certain groups of society, which often do not have the ability to meet their basic needs on their own, and among these groups are orphans and the elderly.